Inflammation, diabetic foot and related treatments - Qin, Yuqi; Deng, Shan (Frontiers in Endocrinology, 2025)
Diabetic foot, one of the most severe chronic complications of diabetes mellitus, arises from complex interactions among neuropathy, vascular ischemia, and inflammatory dysregulation. This review systematically explores the inflammatory regulatory network centered on NF-κB and the interleukin (IL) family in the diabetic foot microenvironment and examines their roles in promoting tissue damage. Under hyperglycemic conditions, the AGE-RAGE axis potently activates the NF-κB signaling pathway, leading to upregulation of pro-inflammatory factors and suppression of anti-inflammatory mediators, thereby forming a vicious cycle of “inflammation-oxidative stress-tissue damage.” Charcot foot, a distinct subtype characterized by neurogenic osteoarthropathy, is strongly linked to abnormal IL-6/RANKL pathway activation and impaired anti-inflammatory neuropeptide signaling. We further assess the diagnostic utility of inflammatory biomarkers, including procalcitonin (PCT), high-sensitivity C-reactive protein (hs-CRP), and the neutrophil-to-lymphocyte ratio (NLR), and summarize current therapeutic challenges along with emerging targeted strategies, such as NF-κB inhibition via salicylates. This review underscores the importance of spatiotemporal heterogeneity and dynamic equilibrium within inflammatory networks for clinical stratification and proposes that integrating multi-omics data with artificial intelligence models holds promise for developing personalized interventions. This approach offers novel theoretical insights to overcome therapeutic bottlenecks in diabetic foot management.